Methods of Education in Islamic Education Recommended - Salamah, Umi (International Conference of Moslem Society, 2016)
The purpose of Islamic education is essentially a form of learners in order to grow as a generation "khoiru ummah" (the faithful, and devoted, mature in attitude, mentality, intellect and spirit of independent living, creative, dynamic and morals karimah) the main problem is how menggembangkan agencies -lembaga Islamic education so that they can become "fertile ground" persemian a new generation of powerful and loaded by the target formations and educational values ​​of the Qur'an.The system of Islamic education at the time of Rasulullah SAW, has the goal of forming a personal protégé of individual Muslim to become good in life so getting welfare and tranquility of life derived from the Qur'an and the Sunnah of Rasulullah SAW.In the learning system at the time of Rasulullah SAW there are some pereode the mecca and educational material madinah. Pembinaan Islam in Mecca emphasized on Aqidah guidance in order to inculcate the values ​​of monotheism to their souls monotheism rays radiated and reflected in the actions and behavior in the everyday life, while the issue of Islamic education in the medina is essentially continuing education of education monotheism in Mecca that is coaching in the field of religious, especially kaitanya in worship, education ahlak, health education, and educational relation with the community, including in the field of social education, and politics so imbued with the teachings of monotheism, so that the social and political behavior is a reflection and the reflection of monotheism.